Acute fuelling and recovery practices of academy soccer players: implications for growth, maturation, and physical performance - Stables, R. G.; Hannon, M. P.; Costello, N. B.; McHaffie, S. J.; Sodhi, J. S.; Close, G. L.; Morton, J. P. (Science and Medicine in Football, 2024)
Academy soccer players frequently train in the evening (i.e. 1700-2000 h), hence limited time to nutritionally prepare and recover due to schooling, travel and sleep schedules. Accordingly, we assessed timing and quantity of energy intake in the pre-training and post-training period. Over a 3-day in-season training period, male players (n=48; n=8 from under (U) 12, 13, 14, 15/16, 18 and 23 players) from an English Premier League academy self-reported dietary intake and physical activity levels (via the remote food photography method and activity diary, respectively) in the four hours pre- and post-training. Timing of pre-training energy intake ranged from 40 ± 28 mins (U15/U16 players) to 114 ± 71 mins (U18) before training and mean carbohydrate (CHO) intake ranged from 0.8±0.4 g.kg-1 (U23) to 1.5±0.9 g.kg-1 (U12). Timing of post-training energy intake ranged from 39 ± 27 mins (U14) to 70 ± 84 mins (U23) and mean CHO intake ranged from 1.6±0.8 g.kg-1 (U12) to 0.9±0.5 g.kg-1 (U14). In contrast to CHO, all age groups consumed sufficient protein intake in the post-training period (i.e. > 0.3 g.kg-1). We conclude academy soccer players habitually practice sub-optimal fuelling and recovery strategies, the consequence of which could impair growth, maturation and physical performance.